2022
DOI: 10.1038/s41388-022-02192-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of NFE2L3 protects against inflammation-induced colorectal cancer through modulation of the tumor microenvironment

Abstract: We investigated the role of the NFE2L3 transcription factor in inflammation-induced colorectal cancer. Our studies revealed that Nfe2l3−/− mice exhibit significantly less inflammation in the colon, reduced tumor size and numbers, and skewed localization of tumors with a more pronounced decrease of tumors in the distal colon. CIBERSORT analysis of RNA-seq data from normal and tumor tissue predicted a reduction in mast cells in Nfe2l3−/− animals, which was confirmed by toluidine blue staining. Concomitantly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…With the continuous development of biomedical technology, tumor immunotherapy has become the fourth most effective treatment method after surgery, chemotherapy, and radiotherapy (Dou et al, 2022;Saliba et al, 2022). The potential of NFE2L3 in tumor immunotherapy was explored further by conducting a correlation analysis between the expression of NFE2L3 and immune characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the continuous development of biomedical technology, tumor immunotherapy has become the fourth most effective treatment method after surgery, chemotherapy, and radiotherapy (Dou et al, 2022;Saliba et al, 2022). The potential of NFE2L3 in tumor immunotherapy was explored further by conducting a correlation analysis between the expression of NFE2L3 and immune characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L3 was observed to be involved in transcriptional regulation and chromatin remodeling of the RNA polymerase II promoter in response to oxidative stress by GO enrichment analysis. Moreover, Saliba et al (2022) found that knockdown of NFE2L3 could prevent inflammation-induced colorectal cancer by regulating the tumor microenvironment. NFE2L3 was identified to be involved in multiple immune pathways in most tumors using GSEA analysis, including: CD22 mediated BCR regulation, FCGR activation, and the creation of C4 and C2 activators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important promoters of tumorigenesis in colon cancer is inflammation 53 . Inflammation starts as a response of the immune system to pathogens or tissue damage; however, perpetuating this response results in increasing the incidence of cancer due to the weakness of the anti‐tumor response because it can release bioactive molecules from tumor microenvironment cells such as chemokines, cytokines, and growth factors—that contribute to constant proliferation and cell survival signals to prevent apoptosis‐metalloproteinases,—as a modifier of extracellular matrix to initiate epithelial‐mesenchymal transition (EMT)—pro‐angiogenic factors, and it can also facilitate other tumorigenesis mechanisms such as genome instability 34,54,55 . Although fibroblasts, immune cells, and endothelial cells produce a large portion of pro‐inflammatory signals as tumor microenvironment components, they have also been shown to play an important role in tumorigenesis promotion through the secretion of cytokines and proteases from CAFs 34 …”
Section: The Molecular Mechanisms Behind the Microenvironment In Tumo...mentioning
confidence: 99%
“…VEGF, vascular endothelial growth factor; HIF1, hypoxiainducible factor-1; TGFβ, transforming growth factor-beta; ECM, extracellular matrix; MMPs, matrix metalloproteinases; RBC, red blood cell (EMT)-pro-angiogenic factors, and it can also facilitate other tumorigenesis mechanisms such as genome instability. 34,54,55 Although fibroblasts, immune cells, and endothelial cells produce a large portion of pro-inflammatory signals as tumor microenvironment components, they have also been shown to play an important role in tumorigenesis promotion through the secretion of cytokines and proteases from CAFs. 34 It has been shown that fibroblasts adjacent to the CRC cells express IL-6, FAPα, and SPINK3 as an inflammation-induced factor in CRC.…”
Section: Inflammation As a Potential Mechanism In Tumorigenesismentioning
confidence: 99%